2012
DOI: 10.1371/journal.pone.0042082
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Sequencing and Characterization of the Floral Transcriptome of Dendrocalamus latiflorus (Poaceae: Bambusoideae)

Abstract: BackgroundTranscriptome sequencing can be used to determine gene sequences and transcript abundance in non-model species, and the advent of next-generation sequencing (NGS) technologies has greatly decreased the cost and time required for this process. Transcriptome data are especially desirable in bamboo species, as certain members constitute an economically and culturally important group of mostly semelparous plants with remarkable flowering features, yet little bamboo genomic research has been performed. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
101
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 163 publications
(188 reference statements)
13
101
0
7
Order By: Relevance
“…miR156 and miR172, for example, regulate this phase change in several model plant species (Chen 2004;Yu et al 2010b). The grass family (Poaceae) has become a model system in comparative genomics, and the available grass genome sequences include Brachypodium distachyon, rice, maize, sorghum and foxtail millet (Peng et al 2010;Bennetzen et al 2012;Zhang et al 2012a;Vogel et al 2010;Schnable et al 2009;Paterson et al 2009;Goff et al 2002;Yu et al 2002). For most of these grasses, miRNAome studies have already been performed (Unver and Budak 2009;Zhang et al 2009;Bedell et al 2005;Reinhart et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…miR156 and miR172, for example, regulate this phase change in several model plant species (Chen 2004;Yu et al 2010b). The grass family (Poaceae) has become a model system in comparative genomics, and the available grass genome sequences include Brachypodium distachyon, rice, maize, sorghum and foxtail millet (Peng et al 2010;Bennetzen et al 2012;Zhang et al 2012a;Vogel et al 2010;Schnable et al 2009;Paterson et al 2009;Goff et al 2002;Yu et al 2002). For most of these grasses, miRNAome studies have already been performed (Unver and Budak 2009;Zhang et al 2009;Bedell et al 2005;Reinhart et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…By comparing the unigenes in the leaves of L. indica with the NCBI database, at least 115 unigenes were discovered that showed homology to known flowering related genes from other plants (Supplementary Table S1). The number of unigenes related to flowering time control in L. indica was slightly greater than the number in Poncirus trifoliate (Zhang et al, 2011), but was significantly lower than that in D. latiflorus (Zhang et al, 2012), which included a large amount of floral meristem identity genes. In this study, homologous genes in the four pathways related to flowering time control were more prevalent than in P. trifoliate and D. latiflorus (Zhang et al, 2011(Zhang et al, , 2012.…”
Section: Discussionmentioning
confidence: 70%
“…The number of unigenes related to flowering time control in L. indica was slightly greater than the number in Poncirus trifoliate (Zhang et al, 2011), but was significantly lower than that in D. latiflorus (Zhang et al, 2012), which included a large amount of floral meristem identity genes. In this study, homologous genes in the four pathways related to flowering time control were more prevalent than in P. trifoliate and D. latiflorus (Zhang et al, 2011(Zhang et al, , 2012. This result showed that the leaf transcriptome may be superior to the floral and floral bud transcriptomes on flowering time control.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In this study, a total of 236,529,278 clean reads and 35.47 Gbs of databases were obtained from Chinese fir transcriptomes, which is much more than any previously published transcriptome research on Chinese fir [23][24][25]43]. Due to a lack of homologous unigenes, the average length of unigenes for non-model plants is usually less than 500 bp [26,44,45]. Surprisingly, the unigenes we assembled revealed a mean length of 520 bp, which is longer than those achieved in previous studies of Chinese fir as reported by Huang et al [43].…”
Section: Sequencing and De Novo Assemblymentioning
confidence: 99%